Rethinking adult ADHD : helping clients turn intentions into actions - Ramsay, J. Russell (American Psychological Association, 2020)
"While negative thinking does not cause ADHD, research shows that cognitive strategies play a key role in maintaining ADHD symptoms. In Rethinking Adult ADHD: Helping Clients Turn Intentions Into Actions, Dr. J. Russell Ramsay provides a first-of-its-kind exploration of the common beliefs that underlie and reinforce ADHD in adults, and offers a blueprint to help clients overcome ADHD symptoms using cognitive behavior therapy. The book explores research on negative thoughts and beliefs in adults with ADHD, specifically the belief, or lack thereof, in one's ability to persistently and consistently carry out the steps required to achieve one's goals. This manifests in what Dr. Ramsay describes as self-distrust thoughts and self-mistrust beliefs, and which leads to escape-avoidance coping patterns. To address these problems, he targets emotional, behavioral, and relationship problems for work in therapy. Clinical case illustrations show how traditional cognitive change tactics can be adapted to treatment of adult ADHD, to foster the implementation of coping strategies and essential skills. These cognitive approaches serve as an essential ligament in treatment, designed to help adults with ADHD more consistently turn their intentions into actions"--